Phyllospongia foliascens-Derived Fungi: Molecular Identification, Antimicrobial Activity and Secondary Metabolite Profile of Their Methanolic Extracts - Putra I Putu Yogi Astara; Ariantari Ni Putu; Wibowo Joko Tri; Leliqia Ni Putu Eka; Dwija Ida Bagus Nyoman Putra; Wulandari Ni Made Widya; Dwijayanti Ni Kadek; Putri Ni Putu Ananda Eka; Dewi Komang Tria Noviana (BIO Web of Conferences)
Sponge-derived fungi are considered a promising source for lead compounds in drug discovery. This study aimed to identify fungi isolated from the sponge Phyllospongia foliascens collected in Amed, Bali, Indonesia, and investigate the antimicrobial activity and secondary metabolites of their methanolic extracts. The identification of pure fungal isolates was done through molecular biology procedure. After rice fermentation of the pure fungal isolates, extraction was carried out using ethyl acetate. The crude extract was subjected to liquid-liquid separation between n-hexane and aqueous methanol. The resulting methanolic phase was dried in vacuo and used for further analysis and antimicrobial assay. Five fungal strains isolated in this study were identified as Aspergillus nomiae SP 1-1-1, Penicillium steckii SP 1-1-2, Penicillium citrinum SP 1-2-4-1, Aspergillus niger SP 1-2-4-2, and Aspergillus sydowii RM-NS-SP-1 (B). Alkaloids were detected in all fungal extracts, while flavonoids and polyphenols were detected in some extracts. Antimicrobial tests employing the disk diffusion method exhibited that P. citrinum SP 1-2-4-1 extract obtained from its fermentation on rice media without salt had pronounced activity against Streptococcus mutans ATCC 35668 with an inhibition zone of 9.61 mm. Meanwhile, the extract afforded from the rice cultures of A. sydowii RM-NS-SP-1 (B) with the addition of salt was active against Staphylococcus aureus ATCC 25923, Methicillin-resistant S. aureus ATCC 3351, and Staphylococcus epidermidis ATCC 12228 with zone inhibitions of 8.27, 2.53, and 5.37 mm, respectively. Thin-layer chromatography-densitometry analysis of both extracts revealed different metabolite profiles, where many peaks were suppressed in the fungal extract obtained from the salt-containing culture.